Gender representations and portrayal of adults in children’s television advertising: content analysis of prime cartoon channels in India - Chitra, Kamalakannan Ravishankaran; Senthilkumar, Nakkeeran (Frontiers in Psychology, 2023)
Introduction Gender stereotyping in television advertising is a universal phenomenon and has the potential to influence children’s perceptions of gender roles. Despite India’s enormous child population, gender representation in television advertising is hardly researched. Methods This study was conducted using a content analysis methodology to examine gender stereotypes in children’s television advertising in India. A total of 189 unique advertisements were selected from six prime cartoon channels, namely Nickelodeon, Disney Channel, Hungama, Cartoon Network, Discovery Kids, and Pogo TV. A stratified constructed sample of 319 central figures from 102 hours of TV viewing was collected over two consecutive weeks in November 2018 during children’s prime-time viewings. Results This study examines gender role cues in children’s television advertising using McArthur and Resko’s coding method. The sample was subsequently analyzed using chi-square statistics, and the findings were contextualized and compared with those from other Asian nations. The results indicated that men significantly dominate (voice-over, product authority, autonomous roles, fact-based arguments, other products, end comments, pleasure, and practical rewards), whereas females are stereotyped (dependent roles, product users, portrayal of domestic products in domestic settings, opinion-based arguments, and self-enhancement rewards). Discussion However, the results reveal a reduction in certain stereotypical aspects, such as a significant increase in women performing voice-overs and portraying characters with product authority and autonomy, while men exhibit increased involvement with domestic products and rewards such as self-enhancement, practical, and pleasure rewards. The theoretical (social learning and role congruity theory) and practical implications for advertisers and marketers are discussed based on these findings.